Spontaneous Ultra-Weak Photon Emission from Human Hands Is Time Dependent - R. V. Wijk; S. Bosman; H. Koch; E. V. Wijk; M. Cifra (Radioengineering, 2007)
Ultra-weak photon emission in the visible range was measured on palm and dorsal side of left and right hand by means of a low noise photomultiplier system. To study the dynamics of this photon emission in a 24 h period photon emission was recorded in 2 h intervals in 5 experiments, utilizing strict protocols for dark adaptation and recording of subjects. Fluctuations in photon emission in the course of 24 h period were demonstrated for each anatomic location. Mean photon emission over the 24 h period differed both between subjects and hand locations. To detect a pattern in the fluctuations the mean value for each location of each subject in each experiment was utilized to calculate fluctuations during the course of 24 h for each anatomical location. The fluctuations in photon emission in the course of 24 h were more at dorsal sides than palm sides. The correlation between fluctuations in palm and dorsal side was not apparent. During the 24 h period a change in left-right symmetry occurred for the dorsal side but not for the palm of the hands. Photon emission at the left dorsal location was high at night, while the right dorsal side emitted most during the day. It is concluded that a daily rhythm in photon emission can be recorded from both the dorsal and palm sides of the hands.